Artificial Intelligence and Cancer Control in Low- and Middle- Income Countries: Relevance in the COVID-19 Era - Gangopadhyay, Aparna (Asian Pacific Journal of Cancer Care, 2023)
Overburdened cancer services in low- and middle-income countries face significant challenges in providing timely interventions for patients with cancer due to limited resources and financial constraints. The COVID-19 pandemic has further exacerbated these challenges, severely impacting cancer services. Many patients have been deprived of timely screening, and treatment delays have resulted from resource reallocation and funding constraints. Artificial intelligence (AI) holds considerable promise in addressing these challenges. AI can reduce screening and treatment times, minimize patient waiting times, increase departmental throughput, and improve the cost-benefit ratio of treatment. In resource-limited settings, the cost savings generated by AI can be reallocated to enhance care services. Given the disruption caused by the pandemic, increased utilization of AI for cancer screening and care can significantly reduce the burden on existing facilities in low- and middle-income countries. This, in turn, can facilitate early diagnosis and treatment, prevent the need for prolonged and intensive treatments, and ultimately improve patient outcomes during this difficult period.